Training Course On Geothermal Electricity - Schütz, Felina; Spalek, Angela (Zenodo, 2012)
Training Course manual: Session I: Market aspects - Constantine Karytsas and Dimitrios Mendrinos Session II: Financial aspects - Gerd Wolter and Thomas Reif Session III – Geothermal exploration and resource assessment - Adele Manzella, Pierre Durst and Jan-Diederik van Wees Session IV: EGS technology - Jan-Diederik van Wees, Chrystel Dezayes and Günther Zimmermann Session V – Geothermal well drilling - Miklos Antics and Pierre Ungemach Session VI – Flash steam and binary technology - Elín Hallgrímsdóttir and Lilja Tryggvadóttir Session VII: Plant operation, energy supply and grid integration - Franz Heilemann and Sören Reith : GEOELEC - IEE : {"references": ["Oskooi, B., Pedersen, L.B., Smirnov, M., \u00c1rnason, K., Eysteinsson, H., Manzella, A., and the DGP Working Group: The deep geothermal structure of the Mid-Atlantic Ridge deduced from MT data in SW Iceland. Phys. Earth Planet. Int., 150, 183-195, 2005.", "Spichak V., and Manzella A.: Electromagnetic sounding of geothermal zones, Journal of Applied Geophysics, 68, 459\u2013478, 2009. doi: 10.1016/j.jappgeo.2008.05.007", "Cloetingh, S., Van Wees, J.D., Ziegler, P.,Lenkey, L., Beekman, F., Tesauro, M., Forster, A., Norden, B., Kaban, M., Hardebol, N., Bonte, D., Genter, A., Guillou-Frottier, L., Voorde, M.T., Sokoutis, D., Willingshofer, E., Cornu, T., Worum, G., 2010. Lithosphere tectonics and thermo-mechanical properties: an integrated modelling approach for Enhanced Geothermal Systems exploration in Europe. Earth-Science Reviews 102, 159-206.", "Bruhn, D., Huenges, E, Agustsson, K, Zang, A, , Rachez, X., Wiemer, S., Van Wees,.J,D..Calcagno, P., , 2011. Geothermal Engineering Integrating Mitigation of Induced Seismicity in Reservoirs - The European GEISER Project. GRC transactions, 39.", "Wassing, B., Van Wees, J.D., Fokker, P., 2012. , Coupled Continuum Modeling of Fracture Reactivation and Induced Seismicity During Enhanced Geothermal Operations. ARMA paper 12-400", "Pierre Ungemach, Convener:, Miklos Antics, Co-convener, Lecturers: Miklos Antics, Peter Eric Danielsen, Hagen Hole and Pierre Ungemach: SHORT COURSE 1 (SC1): DRILLING, COMPLETION AND TESTING OF GEOTHERMAL WELLS. LECTURE NOTES Convener: Pierre Ungemach, Co-convener: Miklos Antics, Lecturers: Miklos Antics, Peter Eric Danielsen, Hagen Hole and Pierre Ungemach; World Geothermal Congress 2010, Bali, Indonesia", "Hole, H.M., 1996. \"Seminar on geothermal Drilling Engineering \u2013 March 1996, Jakarta, Indonesia\", Seminar Text, Geothermal Energy New Zealand Limited, Auckland, New Zealand.", "Gabolde, G., Nguyen, J.P, 1999. \"Drilling Data Handbook \u2013 Seventh Edition\". Institut Francais du P\u00e9trole Publications.", "NZS 2403:1991, \"Code of Practice for Deep Geothermal Wells\" Standards Association of New Zealand", "Ungemach, P. (1995). New Geothermal Concept. IGA News, Newsletter of the Int. Geoth. Ass. Quaterly, 20, January-March, 1995.", "Ungemach, P. (2003). Reinjection of Cool Geothermal Brines into Sandstone Reservoirs, Geothermics, 32, 743-761.", "Hallgr\u00edmsd\u00f3ttir E., Ballzus C. and Hr\u00f3lfsson H. (2012); \"The Hellishei\u00f0i Power Plant, Iceland.\" GRC transaction, Volume 36, page 1067 - 1072", "BDEW. (2012). Ermittlung von Entsch\u00e4digungszahlungen nach \u00a7 12 Abs. 1 EEG 2009. Berlin: Bund deutscher Energiewirtschaft.", "BDEW. (2008). Technische Richtlinien Erzeugungsanlagen am Mittelspannungsnetz - Richtlinien f\u00fcr Anschluss und Paralellbetrieb von Erzeugungsanlagen am Mittelspannungsnetz. Berlin: Bund deutscher Energiewirtschaft.", "BMU. (2011, December 14). Rechtsquellen erneuerbare Energien. Retrieved September 28, 2012, from http://www.res-legal.de/suche-nach-laendern/frankreich/mehr-zum-thema/land/frankreich/ueberblick/foerderung.html", "BMWi. (2012). Energiedaten Deutschland. Berlin: Bundesministerium f\u00fcr Wirtschaft und Technolgie.", "BNetzA. (2011). Abschaltrangfolge, Berechnung der Entsch\u00e4digungszahlungen und Auswirkungen auf die Netzentgelte. Bonn: Federal Network Agency.", "BRD. (2012). Erneurebare Energien Gesetz (EEG). Berlin: Bundesrepublik Deutschland.", "BRD. (1990). Gesetz \u00fcber die Einspeisung von Strom aus erneuerbaren Energien in das \u00f6ffentliche Netz . Bonn: Bundesrepublik Deutschland.", "European Commission. (2012, September 10). Climate Action - The EU Climate and Energy Package. Retrieved September 27, 2012, from http://ec.europa.eu/clima/policies/package/index_en.htm", "European Parliament and the Council. (2003). EU - Directive 2003/54/EC. Brussels: European Parliament and the Council.", "Geothermie Bundesverband. (n.d.). Geothermie in Zahlen. Retrieved October 05, 2012, from http://www.geothermie.de/aktuelles/geothermie-in-zahlen.html", "Konstantin, P. (2007). Praxisbuch Energiewirtschaft. Stuttgart: Springer Verlag.", "Paschen, H., Oertel, D., & Gr\u00fcnwald, R. (2003). M\u00f6glichkeiten geothermischer Stromerzeugung in Deutschland - Arbeitsbericht Nr. 84. Berlin: TAB B\u00fcro f\u00fcr Technikfolgen-Absch\u00e4tzung beim Deutschen Bundestag.", "Tidball, R., Bluestein, J., Rodriguez, N., & Knoke, S. (2010). Cost and Performance Assumptions for Modeling Electricity Generation Technologies. Fairfax: National renewable energy laboratory.", "VDN. (2004). EEG-Erzeugungsanlagen am Hoch- und Mittelspannungsnetz - Leitfaden f\u00fcr Anschluss und Paralellbetrieb von Erzeugungsanlagen auf Basis erneuerbarer Energien an das Hoch- und H\u00f6chstspannungsnetz. Berlin: Verband deutscher Netzbetreiber."]}